TINJAUAN YURIDIS TERHADAP WANPRESTASI DALAM HAL HUTANG PIUTANG - Jon Hendri; Khoiri Khoiri (STIH Putri Maharaja, 2018)
Kaselan S.Hut has lent money to Abdul Wahid bin Kosmol with the amount of money of Rp. 162,000,000. But abdul wahid bin kosmol wanprestasi until finally to the court but in the trial, the “majelis hakim” did not consider the willingness shown by abdul Wahid to pay off the debts to kaselan. The problem of the study was how the judges’s legal considerations in deciding cases Number 1372 K / PDT / 2008 and how about a way to prove the case Number 1372 K / PDT / 2008. Furthermore, the method of this journal was the type of normative research, the source data obtained from three parts of Primary Legal Material, the decision of the Supreme Court and the “Perdata